Public perceptions of radio messages on Malaria Preventive Measures among Rural Dwellers in Osun State - OKO-EPELLE , LYDIA; Talabi, Felix Olajide; Sanusi, Bernice; Oloyede, I.B. (Corpus Intellectual, 2024)
Malaria is a public health issue, and as such, there is a need for constant sensitisation of the populace by the media on the transmission, symptoms, health implications and treatment. Regardless, how the messages on malaria prevention are perceived could affect the adoption or otherwise of the measures. This paper examined public perception of radio messages on malaria measures among rural dwellers in Osun State. The study's objective is to examine how rural dwellers perceive the effectiveness of radio in educating them about malaria preventive measures and their attitude towards adopting the preventive measures. This study used a multiple-stage sampling technique to select 32 participants from Iwo and Ede South Local Government Areas. Findings showed that participants had a good perception of the radio to educate them about malaria preventive measures as they claimed exposure and adoption of the measures. Further findings revealed that participants were most familiar with using insecticide, treated mosquito nets, and anti-malaria drugs, while other measures received low responses. Based on the findings, the study concluded that the media needs to sensitise rural residents to the effectiveness of other measures to achieve the desired change in health behaviour. The study recommended that the radio be considered an effective communication channel for sensitising rural residents on public health issues.